2021
DOI: 10.1093/jrr/rrab029
|View full text |Cite
|
Sign up to set email alerts
|

Health effects triggered by tritium: how do we get public understanding based on scientifically supported evidence?

Abstract: The Commission for ‘Corresponding to Radiation Disaster of the Japanese Radiation Research Society’ formulated a description of potential health effects triggered by tritium. This was in response to the issue of discharging water containing tritium filtered by the Advanced Liquid Processing System (ALPS), generated and stored in Fukushima Daiichi Nuclear Power Station after the accident. In this review article, the contents of the description, originally provided in Japanese, which gives clear and detailed exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…53 Whilst 3 H does not accumulate in specific parts of the body, the 10 day and 40 day biological half-lives of tritiated water and OBT, respectively, make the radionuclide a potential hazard once inside humans. 54 Defining the specific risk that DTMRs pose can be complex due to a number of variables, including the exposure pathway to an individual (inhalation, ingestion, skin contact, etc. ), the body part(s) that come into contact with radiation, the age of the person (children and the elderly may potentially be more affected compared to adults), etc.…”
Section: Dtmrs In the Environmentmentioning
confidence: 99%
“…53 Whilst 3 H does not accumulate in specific parts of the body, the 10 day and 40 day biological half-lives of tritiated water and OBT, respectively, make the radionuclide a potential hazard once inside humans. 54 Defining the specific risk that DTMRs pose can be complex due to a number of variables, including the exposure pathway to an individual (inhalation, ingestion, skin contact, etc. ), the body part(s) that come into contact with radiation, the age of the person (children and the elderly may potentially be more affected compared to adults), etc.…”
Section: Dtmrs In the Environmentmentioning
confidence: 99%
“…As an isotope of hydrogen, tritium forms HTO molecules that behave like water in the body. Once in the body, the biological half-life of tritium is estimated to be about 10 days, as HTO is incorporated into the body and eliminated relatively quickly, like H 2 O [ 3 ]. A fraction of tritium may also be incorporated into organic molecules, forming organically bound tritium (OBT).…”
Section: Introductionmentioning
confidence: 99%
“…A fraction of tritium may also be incorporated into organic molecules, forming organically bound tritium (OBT). OBT can remain in the body for longer periods of time, with two biological half-lives of about 40 days and about a year, depending on the turnover of organic molecules that have incorporated the tritium [ 3 ]. Following OBT formation, the elimination of tritium could be slowed down, resulting in a higher absorbed radiation dose and more severe cell damage.…”
Section: Introductionmentioning
confidence: 99%
“…This is not only of concern to the people who lived around the FDNPP, but also has been an international issue for the past decade. 2 We have observed that the topics of interest related to radiation have gradually changed since the accident. 3 It is essential to pay attention to the most recent topics of concern or interest and to use them to develop effective risk communication efforts and to prepare for future nuclear disasters.…”
mentioning
confidence: 99%
“…This is not only of concern to the people who lived around the FDNPP, but also has been an international issue for the past decade. 2…”
mentioning
confidence: 99%